The combined assessment of p16INK4a and Mib/Ki-67 in oral squamous cell carcinoma - Richter, Maximilian; Doll, Christian; Mrosk, Friedrich; Hofmann, Elena; Koerdt, Steffen; Heiland, Max; Neumann, Konrad; Beck, Marcus; Dommerich, Steffen; Jöhrens, Korinna; Raguse, Jan-Dirk (Frontiers in Oncology, 2024)
ObjectiveDespite numerous studies addressing the impact of p16INK4a in oral squamous cell carcinoma (OSCC), consistent data regarding survival and tumor proliferation behavior are lacking. Although some authors investigate both p16INK4a and Mib/Ki-67 in their cohorts, direct correlations are consistently missing. The aim of this study was to investigate the combined influence of p16INK4a and Mib/Ki-67 status on prognosis in OSCC.Materials and methodsClinical data of all patients diagnosed with OSCC and treated curatively between 2005 and 2011 were collected retrospectively. Tissue microarrays of formalin-fixed paraffin-embedded specimens were stained for p16INK4a and Mib/Ki-67 using the CINtec Histology V-Kit or MIB-1 antibody and correlated with the clinical outcome.ResultsA total of 316 patients, with a mean age of 61.7 years were included. Tumor tissues that were tested p16INK4a positive with low Mib/Ki-67 expression demonstrated a remarkable 5-year survival rate of 83% with an improved RFS compared to all other subgroups (p=0.034; p=0.017; p=0.026) and an improved OS compared to those with high Mib/Ki-67 expression (p=0.026; p=0.020). Cox regression identified the combined p16INK4a and Mib/Ki-67 status as a risk factor on OS (HR 6.25; CI1.26-31.0; p=0.025) and RFS (HR 5.88; CI1.19-29.20; p=0.030).ConclusionThese results underscore the importance of a combined assessment of p16INK4a and Mib/Ki-67 in evaluating the prognosis of OSCC, leading to the identification of distinct subgroups that may serve as risk factors for treatment stratification.